Intralesional cryotherapy for hypertrophic scars and keloids: a review - O’Boyle, Ciaran P (Scars Burn Heal, 2017)
INTRODUCTION: Hypertrophic and keloid scarring remain notoriously troublesome for patients to tolerate and frustratingly difficult for clinicians to treat. Many different treatment modalities exist, signifying the failure of any method to achieve consistently excellent results. Intralesional cryotherapy is a relatively recent development that uses a double lumen needle, placed through the core of a keloid or hypertrophic scar, to deliver nitrogen vapour, which freezes the scar from its core, outwards. METHODS: This article provides a comprehensive review of the literature on intralesional cryotherapy for hypertrophic scars and keloids. A systematic review or meta-analysis was not possible, since the existing articles did not permit this. RESULTS: A search of English language, peer-reviewed literature was carried out. The evidence base was found to be low (level 4). In addition, much of the published evidence comes from a very few groups. Despite this, consistent findings from case series suggest that the technique is safe and achieves good scar reduction with very few treatments. Adverse effects include depigmentation, recurrence and pain. Pain and recurrence appear to be uncommon and depigmentation may be temporary. DISCUSSION: Well-constructed, prospectively recruited comparative trials are absent from the literature. These are strongly encouraged, in order to strengthen general confidence in this technique and in the repeatability of outcomes reported thus far.